Holocene circum-Mediterranean vegetation changes: Climate forcing and human impact (Quaternary International, 2009)
The Mediterranean climate and its variability depend on global-scale climate patterns. Close correlations appear when comparing Holocene palaeoenvironmental data (lake levels, ﬂuvial activity, Mediterranean surface temperature and salinity, marine sedimentation) with the main stages of the history of the circum-Mediterranean vegetation. They indicate an evolution of the Mediterranean biome controlled by the climate and emphasize the teleconnections between the climate of the Mediterranean area and the global climatic system. In the circum-Mediterranean area, the Holocene can be divided into three periods: a lower humid Holocene (11 500–7000 cal BP) interrupted by dry episodes; a transition phase (7000–5500 cal BP) during which occurred a decrease in insolation as well as the installation of the present atmosphere circulation in the northern hemisphere; and an upper Holocene (5500 cal BP—present) characterized by an aridiﬁcation process. Throughout the Holocene, humans used and modiﬁed more or less strongly the environment but the climatic changes were the determining factors of the evolution of the Mediterranean biome. Societies had to adapt to natural environmental variations, their impact on the environment increasing the ecological consequences of the global changes.